The Surface of Mars - Carr, Michael H (Cambridge University Press, 2013)
This book summarizes our knowledge of the morphology of the martian surface and speculates on how the surface evolved to its present state. During the last three decades our knowledge of Mars has increased dramatically. A succession of orbiting spacecraft (Table I) have observed the planet at ever-increasing resolution, rovers have traversed the surface, analyzing and scrutinizing rocks along the way, and ever more sophisticated techniques are being used to analyze increasing numbers of martian meteorites.